Modelling of Hot Metal Forming in the Conditions of Variable Strain Rates and Temperatures - Pietrzyk, M. (Engineering Transactions, 1999)
The model, based on the internal variable theory, describing behaviour of metals during hot plastic deformation, is presented. This model is coupled with a typical thermal-mechanical finite-element solution for hot metal forming processes. Problems connected with simulation of hot forming of steel and aluminium alloys in the variable conditions are discussed. Two types of materials are considered: (i) those showing a delay of the response in transient conditions, (ii) those reaching without delay a new level determined by the equation of state for new conditions of deformation. The model is verified experimentally.